EVALUASI KONDISI JALAN DAN PENANGGANANNYA DI KECAMATAN KOTA SIGLI KABUPATEN PIDIE - Hendra Satrya; Muhammad Isya; Sugiarto Sugiarto (Prodi Magister Teknik Sipil Unsyiah, 2019)
To know the condition of roads in slum area on the sub-districts of Sigli City and what type of handling which will be done so it can be determined the priority of road handling. The benefit of this research is to provide an alternative in selecting the priority of road handling in slum area in accordance with SK of Pidie regent on 2014. Method used is to assess the road condition and type of handling are Bina Marga Method by conducted road condition survey. Priority of road handling will be done by using Multi Criteria Analysis Method. By creating the road condition value, type of handling, accessibility, land use as the selection criteria. The result of this study is the criteria of handling priority determination on the criteria of road condition with value 51,84 %, assessment for road handling with value 18,29 %, assessment for land use with value 15,61 %, and the assessment of accessibility with value 14,25%. In determining the road segment which will be handling the respondents choose Pante Tengoh road section with criteria of road assessment segment which is in poor condition, type of handling is repair or routine maintenance, the accessibility of land use is in the form of trade area. This road is become the respondents selection because the decreased of road service in serving high traffic which cause traffic jam on the spots along the road and this road has not been improved in several recent years.